AB0277 Patient reported outcomes explain the lack of agreement between physician and patient perceived remission in early rheumatoid arthritis. (15th June 2017) - Turk, SA; Rasch, L; Lems, WF; Tuyl, L van; Schaardenburg, D van; Wee, MM ter
Abstract : Background: Rheumatoid arthritis (RA) patients increasingly reach a state of absence of disease activity, or remission. However, the proportion of patients classified as in remission varies substantially between definitions and are often determined by disease activity score (DAS). But, the importance of patients' perspective is increasingly recognized, which often result in discordance between patients and physician assessment. Objectives: To determine how often patients and physicians agree on a state of remission according to different definitions, as well as the difference in patient reported and clinical outcomes between patients in and not in self-perceived remission. Methods: In 84 consecutive early RA patients, Boolean remission, EULAR response and ACR 70 criteria were determined after 12 weeks of treatment with a fixed schedule methotrexate and prednisone. Physician perceived remission (PhR) was defined as a global assessment of ≤20 on a visual analogue scale, phrased: " How active do you think the RA of your patient is today?" . Patient perceived remission (PatR) was phrased as: " Would you say that, at this moment, your disease activity is as good as gone? Yes/no" . In patients in PhR, the change in components of the DAS44 and questions of the Rheumatoid Arthritis Impact of Disease (RAID) and Health Assessment Questionnaire (HAQ) were compared between patients in and not in self-perceived remission. Results: The agreement on remission between patients and physicians was 64% and was dependent of the definition of remission. In Boolean remission, EULAR good response and ACR70 remission agreement was: 86%, 63% and 80% respectively (table). Patients in PhR, the patients in PatR had more improvement on all RAID subdomains. There were no significant differences in clinical outcomes (ESR was significantly different at baseline, but not after 12 weeks; see figure). Conclusions: Two-third of the patients agreed with the physician on being in remission. In all different definitions for remission, this discordance between physician and patient on perceived remission remained similar. Patients in self-perceived remission had more improvement in components of the RAID, but not in clinical outcomes. Further research is needed to identify domains of patients perceived remission. Disclosure of Interest: None declared